Serum sodium levels associate with recovery of kidney function in immune checkpoint inhibitor nephrotoxicity - Tampe, Désirée; Baier, Eva; Hakroush, Samy; Tampe, Björn (Frontiers in Medicine, 2023)
Background: Immune checkpoint inhibitors (ICIs) are novel drugs targeting programmed cell death protein 1-ligand 1 (PD-L1) or its receptor (PD-1). Enhancing the immune system has also been associated with a wide range of immune-related adverse events (irAE). Among them, acute interstitial nephritis (AIN) is a rare but deleterious irAE in the kidney. However, determinants of recovery and long-term kidney function after ICI withdrawal and steroid therapy thereafter remain elusive. Therefore, we here aimed to identify parameters associated with recovery of kidney function in this previous established cohort of AIN in the context of ICI therapy. Methods: We here monitored kidney function over a mean follow-up time of 812 days in comparison with clinical, histopathological and laboratory parameters associated with recovery of kidney function after AIN related to ICI nephrotoxicity. Results: Abundance of intrarenal PD-L1/PD-1 did not correlate with recovery of kidney function. Furthermore, cumulative steroid dose that was initiated for treatment of AIN related to ICI nephrotoxicity was also not associated with improvement of kidney function. Finally, chronic lesions in the kidney including glomerular sclerosis and interstitial fibrosis/tubular atrophy (IF/TA) did not correlate with eGFR change during the follow-up time. However, we here identified that lower levels of serum sodium at time of kidney biopsy were the strongest independent predictor of renal recovery in ICI-related nephrotoxicity. Conclusion: Because low serum sodium levels associated with better improvement of kidney function, these observations might contribute to novel approaches to enhance recovery after AIN related to ICI nephrotoxicity.